O extrativismo vegetal e a saga do baru (Dipteryx alata Vog.) em Sagarana - MG - Alcantara, Rebecca Silva (2020)
Plant extractivism is one of the oldest activities practiced by mankind. Currently its practice by rural populations is based on the family workforce and has been encouraged by a variety of institutions. In the Cerrado Territory, among the various non-timber forest products that can be extracted, baru (Dipteryx alata Vog), a native species, has stood out due to its nutritional characteristics. In Vila de Sagarana, district of the municipality of Arinos located in the northwest of Minas Gerais, this product occurs in high concentrations and due to its market demand and availability of occurrence in the village, it has been gaining prominence among local residents due to income generation for families. Therefore, this research aims to understand the effects of the baru extractive circuit on social and environmental relations in the territory of Sagarana, among those involved in this activity of transforming baru into commodity. This is a qualitative study whose data analysis was based on the interpretation of information collected in the field, combining multiple theoretical and methodological perspectives, together with participatory methods. The actors of this circuit were delineated, namely: collection area owner, collector, the intermediary in the figure of wholesaler and wholesaler and finally gathered information from the final consumer through one of the intermediary agents. In addition to these identified subjects, it was noted that this activity generates socio-environmental conflicts in this territory, which are structured or maintained according to the private ownership of land tenure, the appropriation of natural resources and labor as factors of production and availability. of economic goods. Despite the problematic of this activity, it presents to the collectors a strategy of social reproduction, which evidences the peasants' (re) existence, making activities such as autonomy, knowledge exchange and establishing baru territoriality in Sagarana through its relationship with nature. and the other cultural dimensions.